Pemanfaatan Teknologi Progressive Web Apps (PWA) dalam Pengembangan Sistem Penjualan Satelit berbasis Web (Studi Kasus : PT Pasifik Satelit Nusantara) - Abi Dwijo Sukma; Tibyani Tibyani; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Pasifik Satelit Nusantara is an Indonesian telecommunications and information satellite company and operator. From PT Pasifik Satelit Nusantara, they already have a website that provides information on products & services being sold. However, the website is lacking in helping to make it easier for consumers to be interested in using the products & services provided by PT Pasifik Satelit Nusantara, because the way to access it by manually typing the website address makes users lazy to visit the website, and when the user is in a place with minimal network. , it will be slow loading. To overcome the obstacles that occur, assemble an online business site using the Waterfall technique complete with an order, customer and payment management framework. Not only that, it will be integrated using Midtrans, which is a payment gateway service provider, for automatic payment systems. The implementation of theisystem is builtiin the form of aiwebsite application with the help of the Laravel framework and will also be integrated with progressive web app technology which can be opened on various devices. System testing is done by blackbox.testing and usability.testing. Where in black-box.testing all test cases get valid status. Then the next test, namely usability, was carried out using the usability scale system and got an average of 69.5 in the acceptable category. Testing using Compatibility, the website can be run on various types of browsers. And the test uses Chrome DevTools to test service worker performance on progressive web apps running offline.